2017
DOI: 10.1186/s12906-017-1961-3
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and tea polyphenols combination ameliorate nonalcoholic steatohepatitis in rats

Abstract: BackgroundNonalcoholic steatohepatitis (NASH) is a progressive form of nonalcoholic fatty liver disease, for which there is currently no safe and effective drug for therapy. In this study, we explored the effects of taurine, tea polyphenols (TPs), or a combination thereof, on NASH rats.MethodsRats were divided into a normal group, a high-fat diet induced model group and a treatment group (including taurine, TPs, or taurine + TPs treatment for 8 weeks). Twelve weeks later, all rats were sacrificed, and serum tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Furthermore, to date, we have no single ingredients working efficiently in NAFLD. Several studies performed in animal models of liver steatosis confirm our results (32,33). It has been demonstrated that a mixture of natural citrus polyphenols from Bergamot prevents pathogenic fat accumulation in the liver of rats (11,34).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, to date, we have no single ingredients working efficiently in NAFLD. Several studies performed in animal models of liver steatosis confirm our results (32,33). It has been demonstrated that a mixture of natural citrus polyphenols from Bergamot prevents pathogenic fat accumulation in the liver of rats (11,34).…”
Section: Discussionsupporting
confidence: 87%
“…Combination treatment with taurine and TPs alleviates serum biochemical parameters, such as alanine transaminase and aspartate transaminase, improves histological examination in NASH, and has synergistic effects on lipid disturbance and oxidative stress. These effects were more pronounced than those of taurine or TPs alone . Curcumin, obtained from turmeric extract, was shown to have significant anticarcinogenic and antioxidative effects in experimental studies.…”
Section: Taurine's Combined Usementioning
confidence: 96%
“…Green tea, made from the leaves of the Camillia sinensis plant, like coffee, is commonly consumed and has been well documented to have beneficial effects with NAFLD [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The main therapeutic agent for NAFLD in green tea is epigallocatechin-3-gallate (EGCG) [ 54 , 55 ].…”
Section: Caffeine and Teamentioning
confidence: 99%
“…EGCG also regulates hepatic lipid homeostasis through modulation of mitochondrial complex chain proteins and the previously mentioned AMPK, IRS-1, SREBP, and PPARγ pathways [ 54 , 55 , 60 , 61 ]. Furthermore, the polyphenols and EGCG in green tea allow for an antioxidative effect through NADPH oxidase and cytochrome P450 2E1 (CYP2E1) [ 62 , 63 ]. In the clinical setting, many trials have seen improvements in NAFLD patients with green tea therapy [ 51 , 52 , 57 , 58 ].…”
Section: Caffeine and Teamentioning
confidence: 99%